Growth predictors and prognosis of small abdominal aortic aneurysms - Schlösser, Felix J V; Tangelder, Marco J D; Verhagen, Hence J M; van der Heijden, Geert J M G; Muhs, Bart E; van der Graaf, Yolanda; Moll, Frans L (Journal of vascular surgery, 2008)
Evidence regarding the influence of cardiovascular risk factors, comorbidities, and patient characteristics on the growth of small abdominal aortic aneurysms (AAA) is limited. We assessed, in an observational cohort study, rupture rates, risks of mortality, and the effects of cardiovascular risk factors and patient demographics on growth rates of small AAAs. Between September 1996 and January 2005, 5057 patients with manifest arterial vascular disease or cardiovascular risk factors were included in the Second Manifestation of ARTerial disease (SMART) study. Measurements of the abdominal aortic diameter were performed in all patients. All patients with an initial AAA diameter between 30 and 55 mm were selected for this study. All AAA measurements during follow-up until August 2007 were collected. Multivariate regression analysis was performed to calculate the effects of demographic patient characteristics, initial AAA diameter, and cardiovascular risk factors on AAA growth. Included were 230 patients, with a mean age of 66 years and 90% were male. Seven AAA ruptures (six fatal) occurred in 755 patient years of follow-up (rupture rate 0.9% per patient-year). In 147 patients, AAA measurements were performed for a period of more than 6 months. The median follow-up time was 3.3 years (mean 4.0, range 0.5 to 11.1 years, standard deviation (SD) 2.5). Mean AAA diameter was 38.8 mm (SD 6.8) and mean expansion rate 2.5 mm/y. Patients using lipid-lowering drugs had a 1.2 mm/y (95% confidence interval [CI] -2.34 to -0.060 mm/y) lower AAA growth rate compared to nonusers of these drugs. Initial AAA diameter was associated with a 0.09 mm/y (95% CI 0.01 to 0.18 mm/y) higher growth rate per millimetre increase of the diameter. No other factors, including blood lipid values, were independently associated with AAA growth. Lipid-lowering drug treatment and initial AAA diameter appear to be independently associated with lower AAA growth rates. The risk of rupture of these small abdominal aortic aneurysms was low, which pleads for watchful waiting.